2019
DOI: 10.1159/000496093
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of MicroRNAs in Thymocyte Development

Abstract: MicroRNAs (miRNAs) are a class of endogenous noncoding single-stranded RNAs widely distributed in eukaryotes, which can modulate target gene expression at posttranscriptional level and participate in cell proliferation, differentiation, and apoptosis. Related studies have shown that mi­RNAs are instrumental to many aspects of immunity, including various levels of T-cell immunity. In addition, multiple miRNAs have been ascribed key roles in T-cell development, differentiation, and function. In this review, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…T-lymphocytes, or T-cells, arise from the early T-lineage precursor of the bone marrow that is guided in the thymus to mature and then migrate into peripheral immune tissues to carry out biological functions [ 106 ]. In the thymus, the central immune organ, the development of T-cells is divided into several stages according to the expression of CD4 and CD8 coreceptors [ 108 ].…”
Section: Mirnas and T Cellmentioning
confidence: 99%
“…T-lymphocytes, or T-cells, arise from the early T-lineage precursor of the bone marrow that is guided in the thymus to mature and then migrate into peripheral immune tissues to carry out biological functions [ 106 ]. In the thymus, the central immune organ, the development of T-cells is divided into several stages according to the expression of CD4 and CD8 coreceptors [ 108 ].…”
Section: Mirnas and T Cellmentioning
confidence: 99%
“…Nevertheless, these results demonstrate that miRNAs can modulate T-cell development. Different studies have shown that individual miRNAs are dynamically regulated during T-cell development and maturation as detailed below (25)(26)(27).…”
Section: Mirnas and Thymocyte Developmentmentioning
confidence: 99%
“…The evolution of T cells in thymus is controlled by a complex protein signaling network. Additionally, miRNAs have a significant role in the orchestration of this complex protein signaling network (Hu et al, 2019; Figure 1).…”
Section: Mirnas Involved In T‐cell Development and Selectionmentioning
confidence: 99%
“…miR‐146a establishes the balance between apoptosis and the survival of thymocytes in the DP phase via targeting GTPase, IMAP family member 3 (Gimap3), GTPase, IMAP family member 4 (Gimap4) gene. Subsequently, miR‐146a orchestrates positive selection (Hu et al, 2019; Z. Li et al, 2018). The mouse models have shown that overexpression of miR‐146a leads to the inhibition of the positive selection in thymocytes.…”
Section: Mirnas Involved In T‐cell Development and Selectionmentioning
confidence: 99%
See 1 more Smart Citation